A comparison of the effects of remote coaching HIIT training and combined exercise training on the physical and mental health of university students - Wang, Yu; Jia, Ningxin; Zhou, Yanan; Fu, Linlin; Fan, Lixia; Li, Bin (Frontiers in Psychology, 2023)
Aim To compare the differences in the effects of based on remote coached high intensity interval training and combined exercise training on the physical and mental health of university students. Method Sixty university students were recruited from Shandong Normal University and randomly divided into HIIT group (n = 30) and AR group (n = 30), with the HIIT group using high-intensity interval training intervention and the AR group using combined exercise (aerobic combined with resistance) training intervention for 8 weeks. Mental health indicators, fitness indicators and body composition indicators were measured at the beginning and end of the intervention. Results After 8 weeks, among the mental health indicators, the results of the Symptom Self-Rating Scale (SCL-90) test showed a significant improvement in the HIIT group in terms of total score, somatization, obsessive-compulsive, interpersonal sensitivity, depression, hostility, and psychoticism (p < 0.05); the AR group showed significant improvements in psychoticism (P < 0.05). There were no significant differences between the two groups. The results of the Pittsburgh Sleep Quality Index scale (PSQI) showed a significant difference in sleep efficiency in the HIIT group with an inverse improvement in scores; the AR group showed no significant improvement in each test item. The results of the between-group covariance showed significant differences in sleep efficiency and hypnotic drugs in the HIIT group (p < 0.05). Among the fitness indicators, the HIIT group showed significant improvements in maximum oxygen uptake, grip strength and flexibility (P < 0.05); the AR group showed significant improvements in back muscle strength and flexibility (P < 0.05). The results of the between-group covariance showed significant improvements in maximum oxygen uptake in the HIIT group (P < 0.01). Regarding body composition indicators, there was a significant improvement in Body weight, BMI, Body fat percentage and Waist-to-hip ratio in both the HIIT and AR groups (P < 0.01). There were no significant differences between the two groups. Conclusion HIIT and combined exercise training based on remote coaching had some improvement on fitness level and body composition of university students, HIIT was more advantageous in improving aerobic endurance, and HIIT based on remote coaching may have better effect than combined exercise in mental health. Trial registration Chinese Clinical Trial Register, ChiECRCT20220149. Registered on 16 May 2022.